2021
DOI: 10.3389/fnint.2021.743561
|View full text |Cite
|
Sign up to set email alerts
|

Central Auditory and Vestibular Dysfunction Are Key Features of Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by repetitive behaviors, poor social skills, and difficulties with communication. Beyond these core signs and symptoms, the majority of subjects with ASD have some degree of auditory and vestibular dysfunction. Dysfunction in these sensory modalities is significant as normal cognitive development depends on an accurate representation of our environment. The hearing difficulties in ASD range from deafness to hypersensitivity and subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 127 publications
1
16
0
2
Order By: Relevance
“…The number of overall neurons is also decreased in the MSO and LSO in VPA rats, and the number of inhibitory neurons was decreased in the SPON of Fmr1 −/− rats [ 118 , 153 ]. These results are similar to studies of human brains, which have found fewer and smaller neurons in the SOC of those with ASD, especially in the MSO, where the neurons were also rounder, consistent with an immature phenotype [ 74 , 132 ]. The levels of neurotransmitters glutamate, GABA, and glutamine were not changed in the SOC of Cntnap2 −/− rats [ 84 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The number of overall neurons is also decreased in the MSO and LSO in VPA rats, and the number of inhibitory neurons was decreased in the SPON of Fmr1 −/− rats [ 118 , 153 ]. These results are similar to studies of human brains, which have found fewer and smaller neurons in the SOC of those with ASD, especially in the MSO, where the neurons were also rounder, consistent with an immature phenotype [ 74 , 132 ]. The levels of neurotransmitters glutamate, GABA, and glutamine were not changed in the SOC of Cntnap2 −/− rats [ 84 ].…”
Section: Resultssupporting
confidence: 89%
“…As appealing as ABRs are as a non-invasive measure of function in lower auditory structures, too few studies have performed this test on rodent models of ASD to draw conclusions across different models. ABR measures in children with autism show trends towards lower amplitudes and longer latencies, but there is a significant variation in the response [ 74 , 76 , 136 ]. The inability of rodent studies in various models to converge on a consistent ABR phenotype may therefore be an accurate portrayal of the diversity of ABRs in iASD with a range of aetiologies.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, increased awareness of balance and vestibular problems in children is needed. As stated in a recent publication [ 9 ], “vestibular issues are likely under-reported in children with ASD and may go unrecognized”. That being said, balance and vestibular testing can be very challenging for any child with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…A later study looking at the VOR in children with ASD found abnormalities, which were attributed to alternations in cerebellar and brainstem circuitry [ 8 ]. Central vestibular dysfunction in ASD was highlighted in a recent review study published in 2021 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being observed in response to both pure tones and complex stimuli (such as speech) [ 40 ], the hypothesis was advanced that this difference might precipitate higher-order autistic difficulties in communication [ 42 , 43 ]. Comparing HF and LF, previous studies report better auditory capacities in HF [ 44 ], who can even surpass non-autistic young adults in terms of unexpected and expected sound detection [ 45 ]. On the contrary, the auditory processing in LF could be compromised by a sensory overload, in turn interfering with social communication.…”
Section: Discussionmentioning
confidence: 99%